2000
DOI: 10.1017/s0950268899003866
|View full text |Cite
|
Sign up to set email alerts
|

Silent spread of dengue and dengue haemorrhagic fever to Coimbatore and Erode districts in Tamil Nadu, India, 1998: need for effective surveillance to monitor and control the disease

Abstract: Dengue fever (DF) or dengue haemorrhagic fever (DHF) has not previously been reported in Coimbatore and Erode districts in Tamil Nadu in India. In 1998, 20 hospitalized cases of fever tested positive for dengue virus IgM and/or IgG antibodies. All of them had dengue-compatible illness, and at least four had DHF. Two of them died. Sixteen cases were below 10 years of age. The cases were scattered in 15 distantly located villages and 5 urban localities that had a high Aedes aegypti population. Although the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…In this study, we confirmed the subclinical DEN infections and demonstrated that patients with secondary DEN-2 infections tend to have a higher rate of DHF. This kind of subclinical transmission of DEN infections has also been reported from India (Singh et al, 2000). This suggests that heterotypic secondary DEN infections associated with a higher rate of DHF development may be more frequent in Taiwan and possibly in other Asian countries.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we confirmed the subclinical DEN infections and demonstrated that patients with secondary DEN-2 infections tend to have a higher rate of DHF. This kind of subclinical transmission of DEN infections has also been reported from India (Singh et al, 2000). This suggests that heterotypic secondary DEN infections associated with a higher rate of DHF development may be more frequent in Taiwan and possibly in other Asian countries.…”
Section: Discussionsupporting
confidence: 69%
“…7 Most dengue infections in humans are asymptomatic and silent circulation of dengue virus among human and mosqui-toes has been reported during interepidemic periods of the disease. 8,9 Therefore, understanding the dynamics of dengue transmission before outbreaks may offer a window of opportunity for prevention. Surveillance of dengue transmission in Colombia is made based in a passive system through the notification of disease cases in humans and the survey for variations in Aedes larvae indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, with the introduction of piped water supply, dengue made incursions to rural areas of south India and outbreaks have been reported (Abdul Kader et al . 1997; Singh et al . 2000).…”
Section: Introductionmentioning
confidence: 99%
“…During that time there was little storage of water in villages and therefore Aedes species were scarce (Reuben 1971a,b) and dengue was absent. Subsequently, with the introduction of piped water supply, dengue made incursions to rural areas of south India and outbreaks have been reported (Abdul Kader et al 1997;Singh et al 2000). In rural areas of India, the role of Ae.…”
Section: Introductionmentioning
confidence: 99%